STRATEGI KOMUNIKASI PEMASARAN HIDROPONIA DALAM MENINGKATKAN PENJUALAN SISTEM DAN SARANA HIDROPONIK - IIS SAIDAH (POLITEKNIK PIKSI GANESHA, 2018)
This research uses qualitative method case study wich would give such as with comprehensive about marketing communication strategy hidroponia in increase selling system and medium hidroponik. The result of research show about hidroponia in doing selling marketing strategy that is with doing planning of marketing programme with optimize promotion and supply system and medium hidroponik. Mangement impression whice formed hidroponia that are hidroponia is the place system and medium hidroponik more complete with friendly and quickly service. The model of marketing communication strategy hidroponia in increase of selling show about the activity have been success. The conclusion from this research are plan communication which doing hidroponia have shared more important as a direction guidline in doing marketing communication programme. Management impression which applying base on to increase of selling